"The president has been shot!" : the assassination of John F. Kennedy - Swanson, James L., 1959- (Scholastic Focus, 2021)
Presents an illustrated chronicle of the life and assassination of U.S. President John F. Kennedy. Examines his early years, election, inauguration, and administration before turning to the days, hours, and minutes of the assassination and its aftermath. Features dozens of black-and-white photographs, diagrams, and illustrations as well as sources of further information.